Dekak-Dekak Geometri, Media Pembelajaran Untuk Mengenalkan Bentuk Geometri Pada Anak Kelompok A - Hapsari, Mahda Novita; Ilhami, Baiq Shofa; Agustina, Yulia (Jurnal Golden Age, 2019)
This study aims to produce a learning media Dekak-Dekak Geometric to introduce geometric shapes in group A TK Islam Assa’adah NW Kelayu developmental. This development research used the Borg and Gall development model which is carried out in five stages, the needs analysis, the product development and analysis, the product revision, the field testing phase, and the final product revision. The results of this study indicate that the product developed, dekak-dekak geometry was suitable for learning process. Based on the results of the validation of media, dekak-dekak geometry categorized as "good" with a total score of 38 in the range of scores 37. 398 X ≤ 46. 194. While the results of material expert validation got the category of "pretty good" with a total score of 30 in the range of 26.04 X ≤ 33.96. Based on the results of field trials obtained data of students who get Very Good criteria as many as 9 people, students who get Good criteria as many as 5 people, students who get Enough criteria as many as 1 person, and students who get less criteria as many as 2 people. Student activity data shows that student learning activities are in the "active" category with an average score of 46.411. Based on the results of these studies it can be concluded that the media development products of Dekak-Dekak Geometric media to introduce geometric shapes in children are suitable for use in school learning